2005
DOI: 10.1631/jzus.2005.b1206
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and follow-up of children with transient congenital hypothyroidism

Abstract: Abstract:Objective: To study the clinical therapy and prognosis in children with transient congenital hypothyroidism (CH). Methods: Fifty-seven children with CH diagnosed after neonatal screening were treated with low-dosage levothyroxine (L-T4). Follow-up evaluation included the determination of TT3, TT4 and TSH serum levels and the assessment of thyroid gland morphology, bone age, growth development and development quotients (DQ). A full check-up was performed at age 2, when the affected children first disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 9 publications
1
11
0
6
Order By: Relevance
“…It was thought that the similarity in sex distribution might be related with limited the number of subjects or a finding reflecting a characteristic of the Western regions of Turkey. In the literature, it has been reported that transient PCH occurs more commonly in the male sex (16,18,21). In our study, the number of male subjects was higher and the female/male ratio was 1:2.1 in the transient PCH group, similar to the literature.…”
Section: Discussionsupporting
confidence: 90%
“…It was thought that the similarity in sex distribution might be related with limited the number of subjects or a finding reflecting a characteristic of the Western regions of Turkey. In the literature, it has been reported that transient PCH occurs more commonly in the male sex (16,18,21). In our study, the number of male subjects was higher and the female/male ratio was 1:2.1 in the transient PCH group, similar to the literature.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, these parameters were similar in the groups. Yang et al (15) reported that physical and mental growth following treatment discontinuation in patients with transient hypothyroidism (when they were 2-3 years of age; at the 1-year follow-up) were similar to that of healthy children. Similarly, Demirel et al (16) found age-appropriate normal results in the Denver developmental screening test in patients with hyperthyrotropinemia.…”
Section: Discussionmentioning
confidence: 96%
“…In another study conducted by Dimitropoulos A, authors concluded that using 14.7 μg/kg/d at initiation of treatment led to significant higher IQ compared to the control group (111.4 versus 101.7; P < 0.0001) (19). Despite much data available in favor of using high doses, in one study it was mentioned that a dose of 3.21-5.81 µg/kg/d was adequate for the treatment of transient CH (20) and in another study elevated levels of FT4 were observed in many patients, showing that a systematic higher initial dosage could expose many children to the complications of hyperthyroidism (21). …”
Section: Resultsmentioning
confidence: 99%